Enhancing Tubular Bending Precision Using Torch-assisted Softening Technique: Meningkatkan Presisi Pembengkokan Tubular Menggunakan Teknik Pelunakan Berbantuan Obor - Iswanto Iswanto; Ribangun Bamban Jakaria; Ali Akbar (Universitas Muhammadiyah Sidoarjo, 2023)
Abstract: This study presents a novel approach to improve the precision of tubular bending processes. By integrating a torch burner into the conventional manual bending tool, a method was developed to soften the workpiece prior to bending, effectively reducing defects attributed to forced bending. The research includes manual calculations and SolidWorks simulations for comparative analysis. The proposed tool design, utilizing a 40 mm x 40 mm x 700 mm L-profile iron frame with ASTM A36 material, demonstrated successful bending of pipes with ∅ outside 25 mm and ∅ inside 20 mm, achieving a seamless 180° bend from the initial 0° position. The results highlight enhanced bending accuracy and underline the potential of torch-assisted bending for broader applications in fabrication and manufacturing processes. Highlight: nnovative Integration: Integration of a torch burner with a manual bending tool for enhanced precision in tubular bending processes. Defect Reduction: Softening the workpiece before bending reduces defects associated with forced bending, ensuring higher quality outcomes. Comprehensive Analysis: The study employs both manual calculations and SolidWorks simulations for a thorough comparative analysis, validating the proposed approach's efficacy. Keyword: Precision Improvement, Tubular Bending, Torch-Assisted Softening, Defect Reduction, SolidWorks Simulation